2020
DOI: 10.1002/chem.202003594
|View full text |Cite
|
Sign up to set email alerts
|

Selective Activation of Aromatic Aldehydes Promoted by Dispersion Interactions: Steric and Electronic Factors of a π‐Pocket within Cage‐Shaped Borates for Molecular Recognition

Abstract: Selective bond formationsa re one of the most importantr eactionsi no rganic synthesis. In the Lewis acid mediated electrophile reactions of carbonyls, the selective formation of ac arbonyl-acid complex plays ac ritical role in determining selectivity,w hich is basedo nt he difference in the coordinativei nteraction between the carbonyl and Lewis acid center. Although this strategyh as attainedp rogress in selective bond formations, the discrimination between similarly sized aromatica nd aliphatic carbonyls th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 84 publications
0
18
0
Order By: Relevance
“…9 However, the energy differ- ence in ΔE S between 3a and 3b (ΔΔE S = |ΔE S (3b) − ΔE S (3a)|) was larger in the catalytic system of 1AB (ΔΔE S = 6.6 kcal mol −1 ) than that in 1bB (ΔΔE S = 5.5 kcal mol −1 ). 9 The enhanced stabilization in the inclusion complex 1AB•3b . 2 was attributed to the large dispersion energy.…”
Section: Papermentioning
confidence: 99%
See 2 more Smart Citations
“…9 However, the energy differ- ence in ΔE S between 3a and 3b (ΔΔE S = |ΔE S (3b) − ΔE S (3a)|) was larger in the catalytic system of 1AB (ΔΔE S = 6.6 kcal mol −1 ) than that in 1bB (ΔΔE S = 5.5 kcal mol −1 ). 9 The enhanced stabilization in the inclusion complex 1AB•3b . 2 was attributed to the large dispersion energy.…”
Section: Papermentioning
confidence: 99%
“…This may be because molecular recognition is defined by multiple cooperative non-covalent interactions within the π-pocket. 9 Herein, we propose a new cage-shaped borate catalyst showing improved selectivity for aromatic compounds through the support of machine learning (ML). Recent advances in ML applications to organic synthetic chemistry [13][14][15][16][17] have significantly contributed to the predictions of yields and selectivity, 13,18 sequential searches for optimal reaction conditions, [19][20][21] and reverse structure searches for catalysts, ligands, or transient states, 14,15,[22][23][24] design of asymmetric catalysts, [25][26][27][28][29][30][31][32][33] predictions of site-selectivity for C-H functionalization catalyzed by a pocket-shaped Rh complex, 34 and estimations of the substrate specificity of enzymes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[49,50] Our recent studies have demonstrated its effectiveness in controlling the Lewis acidity of a boron [51,52] or aluminum atom. [53] The Lewis acidity of the cage-shaped borate 1B can be tailored by changing the tethered group (XÀ Y), [54,55] the substituents (R), [52] and/or the π-conjugated system (π) [56][57][58][59] (Figure 1A). Furthermore, the cage-shaped borate 2aB exhibits highly chiral recognition and behaves as a chiral Lewis acid catalyst owing to its inherent helicity.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of photoactivated Lewis acids in mind, we focused on a cage-shaped triphenolic ligand, which has established its effectiveness in controlling the Lewis acidity of a boron [38,39] or an aluminum atom. [40] The Lewis acidity of the cage-shaped borate 1B can be tailored by changing the tethered atom and its substituent (XÀ Y), [41] the substituents (R), [42][43][44] and/or the π-conjugated system (π) (Figure 1B). [45,46] We previously reported that benzofuran-based cage-shaped borate 2B exhibited enhanced catalytic activity under black light irradiation.…”
Section: Introductionmentioning
confidence: 99%